Manajemen dalam Konsepsi Al-Qur’an - Akhmad Sobrun Jamil (Institut Pesantren KH Abdul Chalim Mojokerto, 2017)
To form an ideal management conception, a person must be completely understood. To deliver acomplete understanding, the Qur'an is an undeniable answer. Derived from that understanding, thisresearch investigates: first, how is the essence and principles of management in al-Quran? Secondly,what is the management conception in the Qur'an? This research is a literature research by usinghermeneutic research approach. Operationally, this approach includes maudhu'i, semantic andconclusion stages. This approach is intended for the accuracy of research using the Qur'an as theresearch object. The results obtained from this study is, the Qur’an gives an explanation that theessence of management is to pay attention to a matter (problem), thus the issue is praiseworthy andhaving good consequences. The essence of management derives management principles which consistof justice, trust, accountability and communicative..